Adsorption capacity of sodic- and dendrimers-modified stevensite - Hajjaji, Mohamed; Beraa, Abdellah; Coppel, Yannick; Laurent, Regis; Caminade, Anne-Marie (Clay minerals, 2018)
The adsorption capacities of nano-sized organoclays composed of a stevensite-rich clay (R), phosphorus dendrimers (GC1 and GC2) and Na+-saturated clay were evaluated for their capacity to adsorb chromate and methylene blue (MB) in the range of 298-318 K. The adsorption kinetics and the isotherms were analysed based on kinetic equations and isotherm models and by adopting a non-linear regression procedure. In addition, the organoclays and the Na+-saturated clays were characterized principally by solid-state nuclear magnetic resonance spectroscopy. The pseudo-second-order rate equation described kinetics data well, and the adsorption rates were not limited by the intraparticle diffusion or by the liquid film diffusion. Both chemical species were adsorbed spontaneously (-31 < ΔGT< -10 kJ/mol), but the adsorbents had a high affinity for MB species. The adsorption isotherms of chromate were fitted better by the Freundlich model, while those of MB followed the Langmuir model. Chromate adsorption took place at the edges and the free surfaces of stevensite, particularly at the protonated aluminols. MB was adsorbed as MBH2+ and MB+. The MB protonation occurred at the clay surfaces, and MB+ ions were located at the planar surfaces of stevensite as well as at the external surfaces of aggregates. Moreover, the tetrahedral sheet of stevensite involved in the formation of GC1-based organoclays was the subject of a partial chemical modification.